2007
DOI: 10.1017/s0003055407070499
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Ethnic Diversity Undermine Public Goods Provision?

Abstract: A large and growing literature links high levels of ethnic diversity to low levels of public goods provision. Yet although the empirical connection between ethnic heterogeneity and the underprovision of public goods is widely accepted, there is little consensus on the specific mechanisms through which this relationship operates. We identify three families of mechanisms that link diversity to public goods provision—what we term “preferences,” “technology,” and “strategy selection” mechanisms—and run a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
657
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 935 publications
(687 citation statements)
references
References 47 publications
23
657
7
Order By: Relevance
“…A linear probability model employing only the district dummies as explanatory variables shows that the 36 districts account for 6 per cent of the variation in individual cooperativeness in the game, and for 25 per cent of the variation in cooperativeness across schools. 29 One community characteristic that has been shown to affect individual contributions to public goods (Habyarimana et al 2007) and participation in community activities (Alesina and La Ferrara, 2000) is ethnic fragmentation. Comparing cooperation in the four main geographical areas of Tirana, the Coast,…”
Section: Cooperative Behavior In the Public Goods Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear probability model employing only the district dummies as explanatory variables shows that the 36 districts account for 6 per cent of the variation in individual cooperativeness in the game, and for 25 per cent of the variation in cooperativeness across schools. 29 One community characteristic that has been shown to affect individual contributions to public goods (Habyarimana et al 2007) and participation in community activities (Alesina and La Ferrara, 2000) is ethnic fragmentation. Comparing cooperation in the four main geographical areas of Tirana, the Coast,…”
Section: Cooperative Behavior In the Public Goods Experimentsmentioning
confidence: 99%
“…6 For comprehensive reviews of the experimental literature relating to behavior in public goods experiments see Ledyard (1995) and Chaudhuri (2011). 7 One important society characteristic that has been shown to be negatively correlated with individual contributions to a publi c good (Habyarimana et al 2007), participation in community activities (Alesina and La Ferrara, 2000), community-based monitoring of public service providers (Bjorkman and Svensson, 2010), and local public good provision (Miguel and Gugerty, 2004) is ethnic fragmentation. Neighborhood social and economic inequalities have also been shown to matter for urban violence (Morenoff, Sampson and Raudenbush, 2001) and collective civic action (Sampson et al, 2005). cooperation is also salient.…”
Section: Introductionmentioning
confidence: 99%
“…The connection is often explained by a lack of cooperation across diverse groups, which causes an inefficient use of productive assets in general and a suboptimal provision of public goods in particular (e.g. Alesina et al 1999;Habyarimana et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research has shown that social preferences, which have traditionally been taken by economists as exogenous, are in fact influenced by a variety of environmental factors, which recent economic experiments have sought to identify (Fehr and Hoff, 2011), and a growing literature demonstrates the influence of individual, demographic and cultural characteristics on social preferences (Henrich et al, 2006,;Habyarimana et al, 2007;Fershtman and Gneezy, 2001;Croson and Gneezy, 2009). …”
Section: Theoretical Background and Motivationmentioning
confidence: 99%